Survival of enteroaggregative Escherichia coli and Vibrio cholerae in frozen and chilled foods - Waturangi, Diana Elizabeth; Amadeus, Steven; Kelvianto, Yustinus Ericko (The Journal of Infection in Developing Countries, 2015)
Introduction: Enteroaggregative Escherichia coli (EAEC) and Vibrio cholerae are common bacteria that infect people in developing countries. Nowadays, food preservation by freezing and refrigeration are very common practices that extend the shelf life of food products. Unfortunately, EAEC and V. cholerae are suspected to survive at low temperatures. Methodology: Various foods and beverages used as samples were artificially inoculated with EAEC and V. cholerae pure colonies and incubated at room temperature (27°C), refrigeration temperature (4°C), and frozen temperature (-20°C) for one week, two weeks, one month, two months, and three months. The survival of these bacteria was confirmed by polymerase chain reaction (PCR) with specific primers to detect their virulence genes (aggR for EAEC and toxR for V. cholerae) that represent the presence of these bacteria. Results: This study showed that EAEC was able to survive in all food samples used in this study for at least three months under room temperature, refrigeration temperature, and frozen temperature. V. cholerae had poor survival in almost all food samples over two months under room temperature and over three months under refrigeration temperature. V. cholerae was able to survive in all food samples for at least three months under frozen temperature. Conclusions: The survival of EAEC and V. cholerae in this study should increase our awareness of how hazardous these bacteria are. Therefore, in order to improve food safety and hygiene, advanced preservation and sterilization methods should be discovered to prevent contamination with and survival of EAEC and V. cholerae.